2007
DOI: 10.1098/rspb.2007.1272
|View full text |Cite
|
Sign up to set email alerts
|

A primary role of developmental instability in sexual selection

Abstract: In evolutionary biology, fluctuating asymmetry (FA) is thought to reveal developmental instability (DI, inability to buffer development against perturbations), but its adaptive and genetic bases are being debated. In other fields, such as human clinical genetics, DI is being assessed as incidence of minor morphological abnormalities (MMAs) and used to predict certain fitness outcomes. Here, for the first time, we combine these complementary measures of DI in sexual selection and quantitative genetic studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 49 publications
3
72
0
Order By: Relevance
“…Moreover, fluctuating asymmetry and phenodeviants in Drosophila bipectinata share a common buffering system [176]. Understanding the underlying basis of developmental instability is critically important to the future development of the field [105].…”
Section: Adaptation Coadaptation and Heterozygositymentioning
confidence: 99%
“…Moreover, fluctuating asymmetry and phenodeviants in Drosophila bipectinata share a common buffering system [176]. Understanding the underlying basis of developmental instability is critically important to the future development of the field [105].…”
Section: Adaptation Coadaptation and Heterozygositymentioning
confidence: 99%
“…However, a lack of condition dependence is not the case for the sex comb in D. bipectinata. In fact sex comb size is both heritable and condition dependent, and therefore not surprisingly, also under sexual selection in some populations [35,36]. Condition dependence of the sex comb has been demonstrated in a previous study, in which increased temperature applied during larval development decreased sex comb size [28].…”
Section: Discussionmentioning
confidence: 96%
“…These negative relationships suggest that FA is influenced by a multitude of loci throughout the genome, as body size in Drosophila and other organisms is a complex, multifactorial trait related to fitness [51][52][53][54]. Interestingly, in a field study in New Caledonia, where FA was strongly and consistently shown to be the target of sexual selection, it was FA1, not FA2 or comb size, that predicted male mating success [36]. These differential effects on mating success further support the view that FA and comb size tap distinct properties of the genome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations